Out of sight, out of mind? Testing the effects of overwinter habitat alterations on breeding territories of a migratory endangered species. (22nd March 2018) - Morant, J.; Zabala, J.; Martínez, J. E.; Zuberogoitia, I.
Abstract: Anthropogenic activities are one of the main threats to species living in human‐dominated landscapes and can promote behavioral changes in birds. This paper presents a novel approach to test how a migratory species responds to habitat alterations occurring in nesting territories during winter, when the species is absent. From 2000 to 2016, we collated territory and nest monitoring data for the endangered Egyptian vulture Neophron percnopterus in the north of Spain, to test the effects of overwinter habitat alterations (OHA) around breeding territories on the species reproductive output. We monitored 70 different nest sites and observed OHA around the nesting area in 39 cases. Probability of switching to another nesting site almost tripled after OHA. Pairs that switched experienced substantially decreased breeding success and avoided reusing the nest for 4.8 ± 4.64 years. The presence of determinate landscape elements that provide screening, such as forest patches, increased nest reoccupancy probability after OHA by more than 0.3, to 0. 55 (compared to 0.24 when no screening was present). We also found that the distance and the situation of the OHA were critical factors explaining reproduction probabilities at nest sites. Our results demonstrate how OHA can strongly impact the breeding behavior of long‐lived species. This highlights the need to examine the long‐term impact of OHA rather than focusing only on disturbances during sensitive periods, as is often the case with habitual mitigation measures. Abstract : Anthropogenic activities are one of the main threats to species living in human‐dominated landscapes and can promote behavioural changes in birds. We found that overwinter habitat alterations (OHA), mainly forestry activities, around the nest sites increase habitual nest abandonment probability respecting to those which did not suffer OHA and, in a second step, the situation of OHA reduce reproduction probability and ultimately, productivity of those pairs which switched nest. Therefore it is necessary to adopt management measures that guarantee the persistence (i.e. use of forest patches which act as a screen between OHA and nest site increase reoccupancy probability) and reproduction of species (i.e. avoiding those OHA located in front of the nest sites).